Salto Talaris Total Ankle Arthroplasty: Clinical Results at a Mean of 5.2 Years in 78 Patients Treated by a Single Surgeon. (21st December 2016) - Hofmann, Kurt J.; Shabin, Zabrina M.; Ferkel, Eric; Jockel, Jeffrey; Slovenkai, Mark P.
Abstract : Background: In recent years, the number of total ankle arthroplasty procedures performed has increased dramatically. We sought to report the clinical results of the largest cohort of patients treated with a modern fixed-bearing total ankle arthroplasty by a single surgeon. Methods: We retrospectively reviewed the charts of 78 consecutive patients (81 ankles) who underwent total ankle arthroplasty with a minimum clinical follow-up of 2 years. Sixty-three patients completed standardized questionnaires including the Foot and Ankle Disability Index (FADI), the Short Musculoskeletal Function Assessment (SMFA), the Short Form (SF)-36v2, and a visual analog scale (VAS) for pain. In addition, each patient underwent serial range-of-motion examination and radiographic implant evaluation at each follow-up appointment. Results: Implant survival was 97.5% at a mean follow-up time of 5.2 years. There was 1 revision of a tibial component and 1 revision of a talar component. Thirty-six patients underwent a concurrent procedure at the time of the index surgery, with the most common being removal of previous hardware. Seventeen patients underwent additional procedures following the index surgery, with the most common being gutter debridement. Total range of motion averaged 35.5° preoperatively and 39.9° postoperatively (p = 0.02). Fifty-seven ankles (70%) had >2 years of radiographic follow-up, and 25 ankles (31%) displayed evidence of lucency around a metallic component at the final radiographic follow-up. Outcome scores at a mean of 5.2 years revealed promising results for the cohort, with a mean VAS pain score of 17.7 and a mean FADI score of 79.1. Conclusions: Modern fixed-bearing total ankle arthroplasty had excellent implant survival, improved plantar flexion and total range of motion, and had good-to-excellent functional outcome at a mean follow-up of 5.2 years. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.